BEYOND EYE’S ASSISTIVE TECHNOLOGIES AND PERSONS WITH DISABILITIES (DIVYANGJAN): GLOBAL PUBLIC LIBRARY PERSPECTIVE (LIS TODAY, 2021)
This Paper is prepared to make aware the Person with Visual impairment as well as Librarians who is  serving to visually impaired community about assistive technology. It dwells upon the use and importance of assistive technologies in general and their use for visually Impaired Library users in  particular. Further, it gives suggestions for implementing assistive technologies in Public libraries  for making visually Impaired Library users and self-reliant learners in accomplishing their  academic and research pursuits.
Keywords: Assistive technology (AT); Activities of daily living (ADLs or ADL); Accessible Educational Materials (AEM); Assistive Listening Device (ALD); Audio-Assisted Reading (AAR); Augmentative and Alternative Communication (AAC) System; Digital Talking Book (DTB); Do-It-Yourself (DIY); Emotional and Behavioral Disorder (EBD)